Evidence for the effectiveness of interventions to reduce mental health related stigma in the workplace: a systematic review. Issue 2 (20th February 2023) - Tóth, Mónika Ditta; Ihionvien, Sarah; Leduc, Caleb; Aust, Birgit; Amann, Benedikt L; Cresswell-Smith, Johanna; Reich, Hanna; Cully, Grace; Sanches, Sarita; Fanaj, Naim; Qirjako, Gentiana; Tsantila, Fotini; et al.
Abstract : Objectives: Increasing access to mental health support is a key factor for treating mental disorders, however, important barriers complicate help-seeking, among them, mental health related stigma being most prominent. We aimed to systematically review the current evidence for interventions focusing on reducing stigma related to mental health problems in small and medium enterprises (SMEs). Design: Systematic review with a focus on interventions targeting mental health related stigma in the workplace in accordance with PRISMA guidelines. The methodological quality of included articles was assessed using the Quality Assessment Tool for Quantitative Studies Scale. Data sources: PubMed, Ovid Medline, PsycINFO, Scopus, and Cochrane databases and Google Scholar were searched from January 2010 until November 2022. Eligibility criteria for selecting studies: We included experimental or quasi-experimental studies about workplace interventions aiming to reduce stigma, where the outcomes were measured in terms of stigmatisation against depression, anxiety and/or other mental health problems. Data extraction and synthesis: Records were screened by two independent reviewers after inspecting titles and abstracts and a full-text read of the articles to assess whether they meet inclusion criteria. The results were synthesised narratively. Results: We identified 22 intervention studies, 3 with high quality, 13 with moderate quality and 6 with weak quality. Only 2 studies included SMEs, but no study focused on SMEs exclusively . The mode of delivery of the intervention was face to face in 15 studies, online in 4 studies and mixed in 3 studies. We found a significant reduction in stigmatising attitudes in almost all studies (20/22), using 10 different instruments/scales. Effects seemed to be independent of company size. Online interventions were found to be shorter, but seemed to be as effective as face-to-face interventions. Conclusions: Although we did not find interventions focusing exclusively on SMEs, it is likely that antistigma interventions also will work in smaller workplaces. Trial registration: PROSPERO: ID: CRD42020191307